Economic valuation of ecosystem services of selected interventions in agriculture in India - Kumara T M, Kiran; Birthal, Pratap Singh; Meena, Dinesh Chand; Kumar, Anjani (International Food Policy Research Institute, 2024)
Agriculture is multi-functional, producing economic goods including food, feed, fibre, and fuel, as well as providing several intangible or non-tradable services to society free of cost. Non-tradable services, unlike economic goods, remain unpriced; as a result, farmers are not compensated monetarily for the benefits of the several non-tradable services they provide through agriculture. Recognizing the monetary value of non-tradable ecosystem services is crucial to incentivize farmers to adopt eco-friendly technologies and practices for the sustainable development of agriculture. Through a meta-analysis of the existing evidence on ecosystem services, this study attempts to estimate the value of ecosystem services by using direct and indirect valuation methods—for example, carbon sequestration, methane emission, nutrient availability, biological nitrogen fixation, and water saving—generated by several important technological and agronomic interventions, namely the direct seeding of rice (DSR), zero-tillage in wheat, leguminous crops, organic manure, integrated nutrient management, and agroforestry, based on studies conducted in India. It also explores the trade-offs between the non-tradable and tradable ecosystem services attributable to these interventions. The monetary value of the non-tradable services resulting from most of these interventions is quite large, 34–77% of the total value of all the ecosystem services. However, not all interventions result in a win-win situation that yields improvements in both tradable and non-tradable outcomes. While no-till wheat, legumes, and integrated nutrient management result in a win-win outcome, there are trade-offs between the tradable and non tradable ecosystem services in the cases of directed seed rice, organic manure, and agroforestry. This evidence suggests that not all agricultural technologies and practices are beneficial for farmers, despite their higher environmental benefits. Thus, the findings of this study imply that agricultural policy should provide incentives for the adoption of technologies and practices to conserve ecosystems and natural resources.